2016
DOI: 10.1111/ejss.12359
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term management changes topsoil and subsoil organic carbon and nitrogen dynamics in a temperate agricultural system

Abstract: SummarySoil organic carbon (SOC) and nitrogen (N) contents are controlled partly by plant inputs that can be manipulated in agricultural systems. Although SOC and N pools occur mainly in the topsoil (upper 0.30 m), there are often substantial pools in the subsoil that are commonly assumed to be stable. We tested the hypothesis that contrasting long‐term management systems change the dynamics of SOC and N in the topsoil and subsoil (to 0.75 m) under temperate conditions. We used an established field experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 40 publications
0
57
0
Order By: Relevance
“…Poeplau et al [61] calculated accumulations of SOC of 10 to 50% within 10 years from arable to grass and arable to woodland land use conversions, which covers the kinds of proportional increases we found here (up to 12% increase in the 0-0.3 m depth and up to 43% increase in the 0.3-1.0 m depth from 4 to 6 years). The subsoil may also be affected by land use change [61,62] and accumulation rates may be greater where the subsoil SOC stock was low initially [17]. Berhongaray et al [43] also calculated greater sequestration rates under SRC willow and poplar at 0.3-0.6 m depth compared to 0-0.3 m depth.…”
Section: Soc and Tn Under Bioenergy Cropsmentioning
confidence: 99%
“…Poeplau et al [61] calculated accumulations of SOC of 10 to 50% within 10 years from arable to grass and arable to woodland land use conversions, which covers the kinds of proportional increases we found here (up to 12% increase in the 0-0.3 m depth and up to 43% increase in the 0.3-1.0 m depth from 4 to 6 years). The subsoil may also be affected by land use change [61,62] and accumulation rates may be greater where the subsoil SOC stock was low initially [17]. Berhongaray et al [43] also calculated greater sequestration rates under SRC willow and poplar at 0.3-0.6 m depth compared to 0-0.3 m depth.…”
Section: Soc and Tn Under Bioenergy Cropsmentioning
confidence: 99%
“…Soil organic matter losses coincide with a shift from perennial plant systems to annual cropping systems that introduced frequent tillage, subsurface drainage, and differences in organic matter inputs, including considerably different rooting systems (Davidson and Ackerman, 1993;Huggins et al, 1998;Guo and Gifford, 2002). The effects of changes in soil management, such as increased soil disturbance and aeration, the addition of fertilizers, and changes in residue amount and quality, have often been cited as primary factors in the changes of soil organic matter from native levels (Buyanovsky et al, 1987;Huggins et al, 1998;David et al, 2009;Gregory et al, 2016). The role played by changes in rooting systems, on the other hand, is difficult to study and has received less attention.…”
Section: Introductionmentioning
confidence: 99%
“…The 13 C of grass sampled in 2011 and 2012 (−29.0 to −29.8‰) was 1-2‰ smaller than the 13 C for arable crops grown at the Askov Lermarken site (Bol et al, 2005;Kanstrup et al, 2011). Similarly, Gregory et al (2016) found more negative values for grass than for wheat plant material in an experiment at Rothamsted Research, Harpenden, UK. A selective accumulation of recalcitrant plant residue components that has small 13 C content (e.g.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, Gregory et al . () found more negative values for grass than for wheat plant material in an experiment at Rothamsted Research, Harpenden, UK. A selective accumulation of recalcitrant plant residue components that has small 13 C content (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation